(untitled) (Journal of Analytical Oncology, 2019)
Electrolyte imbalance specifically hypomagnesaemia and hypocalcemia are known events in patients on chemo therapy. We studied thirty- one patients with head and neck cancer who underwent concurrent chemoradiation. Our study has shown that monitoring of calcium and magnesium are equally important and one needs to keep a close watch to avoid morbidity. Objectives: To study and follow the serum magnesium and calcium levels at onset, at different dosage levels of cisplatin and after completion of cisplatin therapy for head and neck cancer patients receiving concurrent radiation. Materials and Method: Serum Calcium and Magnesium levels for thirty-one patients receiving cisplatin based chemotherapy and concurrent radiation were studied. The range of radiation dose was from 56-66 GY/week/30 hrs and cisplatin dose was 40 mg/m2/week. The evaluation was carried out for six consecutive cycles. There was death of one patient during the study. Results: The results showed a reduction in serum calcium and magnesium levels over the treatment period (P = 0.005) with significant error being < 10^-8.